Developer's Responsibility To Banks And Customers In Home Ownership Credit (Kpr) Agreements With Buy Back Guarantees - Puspita, Ratna (Universitas Islam Malang, 2024)
Abstract : Buy back guarantee is a guarantee from the developer for mortgage repayment provided by the bank to customers / debtors by buying back housing units purchased by buyers / customers. In practice, the buyback made by the developer from the bank is in accordance with the remaining debt(outstanding) of the last home ownership loan in the bank. This means that the buy back guarantee made by the developer is the price of the house at the time of purchase minus the down payment cost of the house that has been received by the developer and the installment of home ownership loans that have been received by the bank from customers. The purpose of this study is to analyze the developer's responsibility to banks that provide Home Ownership Loans (KPR) to customers with a buy back guarantee and to analyze the legal protection of customers in buying back guarantees for down payments that have been paid to developers and credit installments that have been paid to banks. This research uses normative juridical research methods or doctrinal legal research, namely research that emphasizes the analysis of legal issues by using legal principles, laws and literature materials related to the legal issues researched and analyzed in this study.The result of this study is the developer's responsibility for banks that provide Home Ownership Loans (KPR) to customers with a buy-back guarantee guarantee is to carry out a buyback of the house that is collateral by paying the remaining debt from the customer to the bank. Legal protection for customers in buying back guarantees for advances that have been paid to developers and credit installments that have been paid to banks has not been regulated in the legislation, so that the status of advances in the event of cancellation of the agreement (default) by the buyer is the buyer / customer Cannot ask for back the down payment that has been given to the seller. In addition, the developer only returns to the buyer/customer the mortgage installment money that the buyer/customer has paid to the bank, because it is considered a customer's risk as a defaulting debtor.Keywords : Responsibility, Home Ownership Credit, Buy Back Guarantee